Nucleic Acid Detection by a Target-Assisted Proximity Proteolysis Reaction - Park, Hyeon Ji; Yoo, Tae Hyeon (ACS Sensors, 2018)
Nucleic acid analysis plays an important role in diagnosing diseases as well as understanding biology. Despite advances in technology, there is still a need to develop a rapid and simple method to detect specific nucleic acids, especially in remote locations and low-resource cases. Here, we proposed a proximity proteolysis reaction in which the reaction between protease and zymogen is enhanced in the presence of a target molecule. The pair of proteins was site-specifically modified with oligonucleotides, and the conjugates were used to develop a method of detecting nucleic acids. Target DNA and RNA could be detected in less than 1 h at sub-nanomolar concentrations based on an absorbance signal. The assay method was resistant to interference by biological matrixes, and its sensitivity could be improved when combined with an isothermal nucleic acid amplification method. The results demonstrated the feasibility of this proximity proteolysis reaction as a new platform technology for detecting specific nucleic acid sequences.
Keywords: Nanomolar concentration; Nucleic acid analysis; Nucleic acid detection; Platform technology; protease; proximity proteolysis reaction; Site-specific; zymogen; Cephalosporins; DNA; DNA, Single-Stranded; Limit of Detection; Nucleic Acid Hybridization; Peptide Hydrolases; Potyvirus; Proteolysis; RNA; Viral Proteins; biosensor; nucleic acid; protease; proximity proteolysis reaction; site-specific conjugation; zymogen